Evaluation of Countinance Stake on the Implementation of Project Based Learning in the Automotive Engineering Department - fajar, Fajar Riyaddi; Waskita; Ambiyar; Lapisa, Remon (The Indonesian Journal of Computer Science, 2023)
Evaluation as an action to find out or an attempt to see the extent to which the goals set have been achieved. In other words, the goal is a tool to determine the success of the learning process that occurs between educators and students. The purpose of this study was to look at the results of the evaluation of project-based learning in productive subjects for students majoring in automotive at the 1 Pantai Cermin Vocational High School. This type of research is evaluative research using a qualitative approach. The evaluation method used is the STAKE method, which evaluates plans, processes and results. The findings of this study, namely, that project-based learning has been implemented for students in the automotive major at Pantai Cermin Vocational High School 1 found that the implementation of project-based learning still has deficiencies in terms of preparation and results. Viewed from the preparation aspect, it was found that the project delivery from the teacher was unclear and not specific, while from the results aspect, the projects undertaken were still limited to video tutorials that had not been published. The conclusion from this research is that project-based learning still needs careful planning to match the expected results or objectives.